Suicide prevention. - Kapur, Navneet; Goldney, Robert D. (Oxford : Oxford University Press, 2019)
Suicide is a major cause of death worldwide, and its impact has only been fully appreciated in the past few decades. This text provides a review of the diverse theories surrounding suicide prevention and looks at management strategies that reduce suicidal behaviours.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 1, 2019).
Keywords: Suicide -- Prevention; Suicidal behavior -- Prevention; Suicide -- Psychological aspects